2019
DOI: 10.1021/acs.est.9b04331
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Water- and Methanol-Soluble Organic Compounds Emitted from Residential Coal Combustion Using Ultrahigh-Resolution Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Water-soluble organic compounds (WSOC) and methanol-soluble organic compounds (MSOC) in smoke particles emitted from residential coal combustion were characterized by ultrahigh-resolution mass spectrometry. The results showed that the molecular compositions of WSOC and MSOC are different. S-containing compounds (CHOS and CHONS) are found to be the dominant components (65–87%) of the WSOC, whereas CHO and CHON compounds make a great contribution (79–96%) to the MSOC samples. It is worth noting that greater abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 77 publications
11
87
0
Order By: Relevance
“…A red shift in the excitation-emission maximum could indicate increased aromaticity and higher molecular weight (Ghidotti et al, 2017). Field observations have demonstrated that chromophore components were associated with chemical structures (Chen et al, 2016a, b;Stubbins et al, 2014). Chen et al (2016b) illustrated that the fluorescent components of HULIS-1 and HULIS-2 were correlated positively with CO + and CO + 2 and C x H + y and C x H y O + 1 groups ions, respectively, using the correlation analysis of the relative intensities of ion groups in high-resolution aerosol mass spectrometers (HR-AMSs) and the relative content of fluo- rescence components.…”
Section: Link Of Molecular Compositions and Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A red shift in the excitation-emission maximum could indicate increased aromaticity and higher molecular weight (Ghidotti et al, 2017). Field observations have demonstrated that chromophore components were associated with chemical structures (Chen et al, 2016a, b;Stubbins et al, 2014). Chen et al (2016b) illustrated that the fluorescent components of HULIS-1 and HULIS-2 were correlated positively with CO + and CO + 2 and C x H + y and C x H y O + 1 groups ions, respectively, using the correlation analysis of the relative intensities of ion groups in high-resolution aerosol mass spectrometers (HR-AMSs) and the relative content of fluo- rescence components.…”
Section: Link Of Molecular Compositions and Optical Propertiesmentioning
confidence: 99%
“…With the advantage of ultrahigh resolution, the accuracy of mass measurements, and high sensitivity (Feng et al, 2016), FT-ICR MS has been successfully used to characterize organic aerosols (Jiang et al, 2016;Song et al, 2018;Mo et al, 2018), cloud water (Zhao et al, 2013), and natural organic matter (Sleighter et al, 2012;Feng et al, 2016). For example, a previous study has determined their molecular families of dissolved organic matter (DOM) associated with fluorescent components by using FT-ICR MS (Stubbins et al, 2014), which could provide more chemical information about chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…EEM analysis enables the probing of the chemical structure of DOM because of its ability to distinguish among different classes of organic matter (Wu et al, 2003). Generally, BrC absorption is related to the chromophores within it and is susceptible to change with variations in chemical properties, e.g., oxidation level (Mo et al, 2018), degree of unsaturation (Jiang et al, 2020), molecular weight (Tang et al, 2020b;Di Lorenzo et al, 2017), functional groups (Chen et al, 2017b), molecular composition, etc (Song et al, 2019;Lin et al, 2018 (Huo et al, 2018). As a linear relationship between organic matter concentration and fluorescence intensity can be assumed for very dilute samples due to the IFE (Murphy et al, 2013), we have corrected our fluorescence data for IFE using absorbance to enable "clean " correlation analysis (as shown in Fig.…”
Section: Chromophores Responsible For Brc Light Absorptionmentioning
confidence: 99%
“…The urban regions are mainly affected by anthropogenic emissions. Therefore, urban BrC may contain (Srinivas and Sarin, 2013;Bosch et al, 2014;Zhang et al, 2017b), rural sites (Hecobian et al, 2010;Kirillova et al, 2014a;Zhu et al, 2018;Xie et al, 2019) and urban sites (Kirillova et al, 2014b;Yan et al, 2015;Chen et al, 2018;Huang et al, 2018;Park et al, 2018). a large amount of aromatic chromophores with a high conjugation degree, which absorb light at a longer wavelength and have lower AAE values (Lambe et al, 2013;Wang et al, 2018).…”
Section: Source Apportionment Of Brcmentioning
confidence: 99%